2016
DOI: 10.1371/journal.pone.0166190
|View full text |Cite
|
Sign up to set email alerts
|

Honey Bee Viruses in Wild Bees: Viral Prevalence, Loads, and Experimental Inoculation

Abstract: Evidence of inter-species pathogen transmission from managed to wild bees has sparked concern that emerging diseases could be causing or exacerbating wild bee declines. While some pathogens, like RNA viruses, have been found in pollen and wild bees, the threat these viruses pose to wild bees is largely unknown. Here, we tested 169 bees, representing 4 families and 8 genera, for five common honey bee (Apis mellifera) viruses, finding that more than 80% of wild bees harbored at least one virus. We also quantifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
92
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(104 citation statements)
references
References 44 publications
10
92
2
Order By: Relevance
“…It has also been demonstrated that pollen pellets collected from foraging honey bees contain viruses that can be used to infect naïve bee colonies (Singh et al, 2010). The health consequences of the diseased status of solitary bees are virtually unknown, though a recent caged-bee study found that a multivirus inoculum caused extreme mortality in honey bees but not in two species of solitary bees (Dolezal et al, 2016).…”
Section: Viral Presencementioning
confidence: 99%
See 2 more Smart Citations
“…It has also been demonstrated that pollen pellets collected from foraging honey bees contain viruses that can be used to infect naïve bee colonies (Singh et al, 2010). The health consequences of the diseased status of solitary bees are virtually unknown, though a recent caged-bee study found that a multivirus inoculum caused extreme mortality in honey bees but not in two species of solitary bees (Dolezal et al, 2016).…”
Section: Viral Presencementioning
confidence: 99%
“…It was not until the 2000s that viruses had been characterized in populations of wild bees and other nonmanaged bee hosts, and it is still most common to measure presence of a virus and not the active infection of the host. Recently this topic has been more actively pursued, and the impact of viruses on the health of native and solitary bees is an emerging field of interest (Singh et al, 2010;Li et al, 2011;Peng et al, 2011;Levitt et al, 2013;Fürst et al, 2014;Ravoet et al, 2014;Graystock et al, 2015;McMahon et al, 2015;Dolezal et al, 2016;Graystock et al, 2016;Tehel et al, 2016;Alvarez et al, 2017;Melathopoulos et al, 2017;Radzeviciute et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to obtain sufficient quantity of honey and hive products, availability of sufficient forage with diverse floral diet, is important for honey bee survival and pathogen resistance [20,21]. However, ecological degradation of the natural resources [22], change in landscape use through intensive agriculture, and the control of weedy plant species [20,23], alongside seasonal drought [24,25] have led to the depletion of bee forage. As a result, apiarists' resort to move their colonies from one area to another in search of nectar and pollen sources in order to maintain honey flow [25].…”
Section: Introductionmentioning
confidence: 99%
“…To date, reviews of the most common RNA viruses in wild pollinator species (Manley et al, 2015;Tehel et al, 2016) suggest that they have a broad host range and thus are potential candidates for cross-species transmission. Previous studies have shown that the most widespread honey bee-associated RNA viruses, the DWV complex and BQCV, infect bumble bees (Fürst et al, 2014, Peng et al, 2011, but very little is known as to whether other wild bee species can also serve as host for these viruses (Dolezal et al, 2016, Manley et al, 2015, Tehel et al, 2016. Earlier studies have been limited by small sample sizes, limited taxonomic breadth, and limited geographic range, with the focus on a few Western European countries and the United States (e.g.…”
Section: Introductionmentioning
confidence: 99%